Developments and Innovation in Carbon Dioxide (Co2) Capture and Storage Technology - Maroto-Valer, M. M. (Abingdon : CRC Press, 2010)
Annotation The fossil-fuel power sector and energy-intensive industries are major producers of carbon dioxide (CO2) emissions, contributing to rising global CO2 levels that have been linked to climate change. CO2 capture and storage (CCS) technology is therefore being developed for application to power plants and in CO2-intensive industries to reduce the carbon footprint of these activities and mitigate the potentially harmful effects of climate change. Developments and innovations in this field are aimed at increasing the effectiveness and lowering the cost of capture and at verifying the safety and efficacy of storage/sequestration. CO2 capture options range from post- and pre-combustion separation to advanced combustion-based options, which are applicable to both new-build power plants and as a retrofit to existing plants, and can also be adopted in other industries. CO2 storage options range from geological sequestration in deep saline aquifers and utilization of CO2 for enhanced oil and gas recovery to mineral carbonation and biofixation. Drawing on a distinguished international team of contributors, this comprehensive reference explores the state of the art of research, development, and demonstration of CCS technology in the power sector industry. It reviews the economics, regulation, and planning of CCS for power plants and industry and examines developments and innovation in post- and pre-combustion and advanced combustion processes and technologies for CO2 capture in power plants. This coverage is extended with sections on CO2 compression, transport, and injection as well as industrial applications of CCS technology, including in the cement, concrete, iron, and steel industries.